Kelayakan Media Pembelajaran Fisika Berupa Buku Saku Berbasis Android pada Materi Fluida Statis - Damayanti, Almira Eka; Syafei, Imam; Komikesari, Happy; Rahayu, Resti (Universitas Islam Negeri Raden Intan Lampung, 2018)
Abstract:This research aims to; know the feasibility of physics learning media in the form of pocket book based on android on static fluid material. This research uses research and development (R and D) method with Borg and Gall model which adapted from Sugiono development model. The data of this study were obtained from questionnaires of educators and learners' responses, questionnaire validation of material experts and media experts. The type of data produced is qualitative data which is analyzed by guidance criteria of assessment category to determine product quality. The result of this study is based on the assessment of the average material percentage of 79,85% worthy of the assessment criteria, the media expert's assessment of the average percentage of 87.96% of the category is very reasonable and the assessment of teachers of SMA / SMK assessment of the average percentage of 87.77% category is very feasible, while the respondents' responses to the three schools average percentage value of 83.92% very feasible category. Based on the assessment by material experts, media experts, educators and students' response, it can be concluded that the android-based physics pocket book worthy of use as a medium of learning. Abstrak:Penelitian ini bertujuan untuk; mengetahui kelayakan media pembelajaran fisika berupa buku saku berbasis android pada materi fluida statis. Penelitian ini menggunakan metode penelitian dan pengembangan (R and D) dengan model Borg and Gall yang diadaptasi dari model pengembangan Sugiono.Data penelitian ini diperoleh dari angket respon pendidik dan peserta didik, angket validasi ahli materi dan ahli media. Jenis data yang dihasilkan adalah data kualitatif yang dianalisis dengan pedoman kriteria kategori penilaian untuk menentukan kualitas produk.Hasil penelitian ini berdasarkan penilaian ahli materi penilaian persentase rata-rata 79,85% kategori layak, penilaian ahli media penilaian persentase rata-rata 87,96 % kategori sangat layak dan penilaian guru SMA/SMK penilaian persentase rata-rata sebesar 87,77% kategori sangat layak, sedangkan respon peserta didik ketiga sekolah nilai presentase rata-rata sebesar 83,92% kategori sangat layak. Berdasarkan penilaian oleh ahli materi, ahli media, pendidik danrespon peserta didik maka dapat disimpulkan bahwa buku saku fisika berbasis android layak digunakan sebagai media pembelajaran.